Dispersion Characteristics of SH waves in a Rotating Micro-structured Plate with Restrained Boundaries - Kaur, Mandeep; Kumar, Satish; Sharma, Vikas (Archives of Acoustics, 2026)
Shear horizontal (SH) waves in plates are elastic stress disturbances that propagate along bounded surfaces, with in-plane shear motion perpendicular to the propagation direction, influenced by physical, geometric, and boundary conditions. Due to their sensitivity to surface and subsurface defects, SH waves are widely employed in non-destructive testing (NDT), structural health monitoring (SHM), and material characterization. This study presents a theoretical investigation of SH-wave propagation in a rotating, microstructural elastic plate within the framework of Consistent Couple Stress Theory (CCST), incorporating elastically restrained boundary conditions. CCST introduces a characteristic length parameter to account for microstructural and size-dependent effects beyond classical elasticity. Restrained boundaries provide an intermediate model between idealized traction-free and rigid conditions, capturing realistic boundary behavior encountered in practical applications. An analytical dispersion relation is derived to examine the combined effects of boundary restraints, microstructural parameters, and rotational speed on SH-wave dispersion, with several special cases presented to validate the general formulation. Graphical results illustrate the influence of restraint stiffness, characteristic length, plate thickness, and rotation on SH-wave dispersion characteristics. The findings offer valuable insights for the design of advanced sensing devices, the development of non-destructive evaluation techniques, and the analysis of seismic wave propagation in rotating geophysical layers.